Voltage stability indices–A comparison and a review. (March 2022) - Salama, Hossam S.; Vokony, István
Highlights: The applications of voltage stability indices (VSIs) in the various power system problems are discussed. The several data for each VSI are presented. Comparative analysis is presented for 49 types of VSIs. Providing a rich source for researchers, students, and employers regarding VSIs. Abstract: The increasing integration of renewable energy sources (RESs) into the power system, rapid load changes, and increasing power demand create problems for the stability of power systems. Therefore, the voltage stability index (VSI) becomes an important indicator of power system stability. This paper provides a comprehensive overview of most VSIs and a wealth of resources for researchers, students, and employers. For each VSI, list data such as name, abbreviation, calculation method, assumptions, the basic concept, steady-state, threshold, instability, pros, and cons are discussed in detail. Also, the paper describes the relationship between RESs, load changes, and VSI, and it investigates the stability issues of the power system. The significant outcome of this comprehensive review is to provide a good foundation for future work in this field and helps professionals to choose the best VSI that meets their needs for various applications. Graphical abstract: Image, graphical abstract